1955
DOI: 10.1172/jci103102
|View full text |Cite
|
Sign up to set email alerts
|

The Acidifying Effect of Rubidium in Normal and Potassium-Deficient Alkalotic Rats 1

Abstract: Rubidium, element number 37, is an alkalimetal found in small quantities in the earth's crust, and in trace amounts in human tissues (1). Listed immediately below potassium in the Group I elements of the periodic table, rubidium possesses many of potassium's physical, chemical, and physiological properties. These two elements have qualitatively similar effects on the contraction of the isolated heart (2), on the depolarization of nerve or muscle preparations (3,4), and on the activity of certain intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
1

Year Published

1957
1957
1972
1972

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 13 publications
2
6
1
Order By: Relevance
“…They also confirm the previously reported fact that rubidium chloride lowers the blood CO2 content in alkalotic potassium-deficient rats (9) and extend the observations to demonstrate a similar, but less marked, acidifying effect of cesium chloride. Most significant of all, however, is the evidence presented here that despite very low plasma concentrations of these ions, muscle tissue may accumulate rubidium or cesium up to concentrations 20 to 60 per cent higher than that of potassium.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…They also confirm the previously reported fact that rubidium chloride lowers the blood CO2 content in alkalotic potassium-deficient rats (9) and extend the observations to demonstrate a similar, but less marked, acidifying effect of cesium chloride. Most significant of all, however, is the evidence presented here that despite very low plasma concentrations of these ions, muscle tissue may accumulate rubidium or cesium up to concentrations 20 to 60 per cent higher than that of potassium.…”
Section: Discussionsupporting
confidence: 91%
“…The foregoing observations confirm and extend the earlier data which had indicated that rubidium and cesium could be taken up in large quantities by muscle cells (6)(7)(8)(9). They also confirm the previously reported fact that rubidium chloride lowers the blood CO2 content in alkalotic potassium-deficient rats (9) and extend the observations to demonstrate a similar, but less marked, acidifying effect of cesium chloride.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Intracellular acidosis has been suggested as an explanation of the increased acid secretion of the potassium-depleted kidney (12)(13)(14). Conversely, it might also be suggested that in the rubidium-loaded animal intracellular pH is normal or increased, since accumulation of rubidium appears to be associated with the movement of acid out of cells (2,4). Renal tissue pH may fall only when the addition of a large exogenous acid load results in a net movement of acid back into cells.…”
Section: Kidney Tissue Analysesmentioning
confidence: 99%
“…In nephrectomized potassium-deficient animals it was demonstrated that rubidium, like potassium, lowers extracellular bicarbonate concentration by displacement of intracellular protons (2) [the latter perhaps transported out of cells by cationic amino acids (3)]. However, clear quantitative differences can be demonstrated between the effects of rubidium and potassium on extracellular bicarbonate: a) chronic administration of RbC1 to potassium-deficient alkalotic rats results in extracellular acidosis, whereas an equivalent amount of KCl merely restores extracellular bicarbonate concentration to normal (2); and b) acute loading of normal rats with RbCl produces a much greater reduction in extracellular bicarbonate than does an equivalent load of KCl (4).…”
mentioning
confidence: 99%